PENGARUH HARGA KHUSUS SURAT KABAR HARIAN (SKH) LAMPUNG POST TERHADAP MINAT BELI MAHASISWA DI BANDAR LAMPUNG (Studi Pada Mahasiswa IBI Darmajaya) - Amanda, Stefani; -, Herlina (Jurnal Manajemen dan Keuangan, 2011)
Efforts marketing strategy is intended to maintain the viability of the company, for it is then necessary to determine appropriate marketing strategies for market segmentation SKH Lampung Post can be maintained or enhanced. SKH Lampung post need to establish appropriate marketing strategies for market segmentation can be maintained.The formulation of this research is whether the special price of Lampung Post SKH effect on consumer purchase interest students in Bandar Lampun Darmajaya IBI. This study aims to measure the level of influence of SKH Lampung Post special prices on consumers buying interest IBI Darmajaya students in Bandar Lampung. The method used in this study is descriptive and associative type of research. The research population of 2167 students Darmajaya then sampled 96 respondents.The results obtained by the regression equation is Y = 0.218 +1.380 X means that the variable rates (X) has a positive influence to enthusiasm buys with regression coefficient of 1.380 means if veriabel rates increase by 1 unit then buying interest will increase by 1.380. There are positive and significant influence of the special price (X) SKH Lampung Post on consumer purchase interest student Darmajaya IBI because tcount> ttable ((7.998)> t table (1.662) sig 0.000 <Î± 0.05.Keyword: Pricing strategy, buying interest